Changes of Goodness into Devil Through Symbolism Authority Reflected on Suzanne Collins' Novel Ballad of Songbirds and Snakes - Septina, Innoria; Rosyidi, Mohamad Ikhwan (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This research aims to understand how authority influences the transformation of a person's character from good to evil, analyzing the impact of social and cultural environments on individual behavior. Using Roland Barthes' semiological theory, this study explores the relationship between signs produced by authority (signifier) and meanings internalized by individuals (signified). Through descriptive qualitative analysis, the research interprets signs based on their literal meanings to identify signifiers and signifieds in character transformation. The findings reveal that external factors such as power dynamics and social status significantly influence Coriolanus Snow's character transformation. The semiotic analysis demonstrates how living conditions create emotional impacts that affect moral development. Furthermore, the symbolism present in the novel illustrates how hope diminishes when confronted with oppressive authority. The findings have broader implications for understanding how power structures systematically influence individual identity formation and moral decision-making processes across various social contexts, contributing to the field of character studies and critical discourse analysisKeywords: Language, Authority, Sign, Morality, Power